2014
DOI: 10.1002/art.38392
|View full text |Cite
|
Sign up to set email alerts
|

ES‐62 Protects Against Collagen‐Induced Arthritis by Resetting Interleukin‐22 Toward Resolution of Inflammation in the Joints

Abstract: ObjectiveThe parasitic worm–derived immunomodulator ES‐62 protects against disease in the mouse collagen‐induced arthritis (CIA) model of rheumatoid arthritis (RA) by suppressing pathogenic interleukin‐17 (IL‐17) responses. The Th17‐associated cytokine IL‐22 also appears to have a pathogenic role in autoimmune arthritis, particularly in promoting proinflammatory responses by synovial fibroblasts and osteoclastogenesis. The present study was undertaken to investigate whether the protection against joint damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
68
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 48 publications
9
68
0
Order By: Relevance
“…Again, underlining the importance of the particular microenvironment, whilst IL-22 appears to play a pathogenic role in the early systemic phase of disease, consistent with findings that mice deficient for IL-22 are resistant to CIA induction, 59 it acts to resolve established inflammation in the joint. 56 Moreover, whilst ES-62 does not significantly modulate levels of IL-22-producing cells in the draining lymph nodes, it increases those pertaining in the joints of animals with established CIA. Indeed, the anti-arthritic effect of ES-62 in the CIA model is dependent on such expression of IL-22, since neutralizing anti-IL-22 antibodies blocked ES-62 protection.…”
Section: Effects Of Es-62 In the Arthritic Joint A Special Environmementioning
confidence: 99%
“…Again, underlining the importance of the particular microenvironment, whilst IL-22 appears to play a pathogenic role in the early systemic phase of disease, consistent with findings that mice deficient for IL-22 are resistant to CIA induction, 59 it acts to resolve established inflammation in the joint. 56 Moreover, whilst ES-62 does not significantly modulate levels of IL-22-producing cells in the draining lymph nodes, it increases those pertaining in the joints of animals with established CIA. Indeed, the anti-arthritic effect of ES-62 in the CIA model is dependent on such expression of IL-22, since neutralizing anti-IL-22 antibodies blocked ES-62 protection.…”
Section: Effects Of Es-62 In the Arthritic Joint A Special Environmementioning
confidence: 99%
“…We have previously shown that ES-62, a phosphorylcholine (PC)-containing immunomodulatory glycoprotein secreted by the filarial nematode Acanthocheilonema viteae , is protective in mouse models of allergic123 and autoimmune456 disease. Such protection is associated with homeostatic resetting of the IL-23/IL-17/IL-22 inflammatory axis, which appears to become dysregulated in these inflammatory disorders: a key effector driving development of this type of inflammation is the dendritic cell (DC), which ES-62 targets by subverting TLR4 signalling789 to suppress aberrant DC-priming of Th17 cells and IL-17-producing γδ T cells24.…”
mentioning
confidence: 99%
“…ES-62 protein derived from A. viteae has been shown to exhibit reduction in the severity of inflammation in collagen induced arthritis (CIA) [1]. The administration of Ascaris suum or the treatment of whole worm extract effectively prevented zymogen induced arthritis in rats with amelioration of clinical symptoms of arthritis and synovitis in a dose dependent manner [19].…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by joint swelling, synovial inflammation and cartilage destruction [1]. Though the aetiology of the disease is not fully understood, dysregulation of IL-17 production and activation of both T and B cells as well as macrophages are supposed to be the cause behind disease progression [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation